Cross of Christ and Hau Monef (Contextualisation of the Cross in the Atoin Pah Meto tribe) - Tari, Ezra (Culture and religion, 2025)
This paper explores the concept of contextualisation of the Cross in the Atoin Pah Meto tribe. The contextualisation effort in this paper is the community’s effort to understand the gospel in culture. Some of the contextualisations are translations into local languages, wearing traditional clothes, and ethnic singing. One of the efforts made by the author is to contextualise the Cross with Hau Monef/Hauteas in the life of Atoin Pah Meto. The author’s search process is to use the qualitative method of the phenomenological approach. The author offers Hau Monef as a substitute for the image of the Cross, which Christians generally know. Hau monef can describe the triune God and the restoration of the relationship between humans, God, and the universe. The connection is re-evaluated in the context of Jesus Christ.